Plant Leaf Disease Detection Robot - Loharkar, Shivam Nilesh; Mahale, Rutik Sandeep; Mahajan, Himanshu Prakasha; Kamble, S. S. (International Journal of Research in Interdisciplinary Studies, 2025)
The key motivation for developing the convolutional networks model for leaf disease is to provide the farmers with an easy-to-use system to detect early-stage infections by using common digital camera. Second, extracting effective features for identifying diseases is a critical but challenging task, and CNNs are highly expected to be automated feature learning from the raw inputs in a systematic way.